The concentration of 12-lipoxygenase in platelet rich plasma as an indication of the cancer of the prostate - Piotrowska, Małgorzata; Szefel, Jarosław; Skrzypczak-Jankun, Ewa; Łysiak-Szydłowska, Wiesława; Szajewski, Mariusz; Aleksandrowicz-Wrona, Ewa; Jankun, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: The aim of this study was to determine whether measuring concentrations of 12-LOX in platelet-rich plasma patients can: 1. Differentiate between the group of patients with prostate cancer and healthy men. 2. Correlate the degree of severity of the disease and the concentration of the enzyme. Material and method s: The study group comprised 88 men (40–88 years), including 54 patients diagnosed with prostate cancer. The population was divided into 4 groups: • group 1 (22 men, aged 55–84 years) –with a negative biopsy, • group 2 (36 men, aged 54–88 years) – with a positive biopsy result, • group 3 (18 participants aged 58–83) – patients with cancer metastatic disease, • group 4 of healthy men (12 people aged 40–66 years) – biopsy was not performed. Routine PSA, morphology and CRP analysis were performed and platelet rich plasma was used for 12(S)LOX determination using an ELISA kit. Results: 1. There was a weak (r = 0.0487) positive correlation between the number of blood platelets and plasma 12(S)LOX. 2. An inverse relationship between 12(S)LOX and Gleason grade was found. 3. Heterogeneity of 12(S)LOX in the group with prostate cancer metastatic disease may suggest differences in the response to the treatment carried out. 4. There were no statistically significant differences in concentrations of 12(S)LOX in different groups of patients. Conclusions : Our results suggest that 12(S)LOX is relevant in prostate cancer; however, further study should include a larger, more select group of men with prostate cancer.